PENGARUH INVESTASI, JUMLAH UANG BEREDAR, INFLASI DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Mukminin, Mikrajul (Journal of Financial Economics & Investment, 2023)
This research aims to analyze the influence of investment, money supply, inflation and interest rates on economic growth in Indonesia. This research approach uses quantitative methods using quarterly data from 2011 to 2022. The data analysis used is time series regression analysis to identify the relationship between these variables and economic growth. The results of time series regression analysis show that investment and money supply have a significant positive influence on economic growth in Indonesia. Besides. Meanwhile, inflation and interest rates do not have a significant effect on economic growth in Indonesia.